Exercise Therapy as Therapeutic Option For Muscle Atrophy: Study on Signaling IGF-1 in Skeletal Muscle - Gifari, Muhammad Yusrin Al; Nafiah, N; Rahmani, R (Annual Physiotherapy Scientific Meeting Proceeding, 2022)
Background - Muscle wasting is caused by metabolic system disorders involving disorders of the musculoskeletal system, one of the risks is insulin growth factor (IGF1) damage. Exercise therapy is one of the physiotherapy interventions that can increase muscle mass and strength, reduce oxidative stress related to aging, chronic inflammation, increase autophagy, and improve mitochondrial function. Methods - The method used in this paper is a literature review using a search database of Google Scholar, Pubmed, and Researchgate with the topic search keywords "muscle wasting", "Biomarker and Molecular IGF1", and "exercise" which are used to expand or specify the search so that it can make it easier in determining the research articles or journals used. literature review selection using inclusion and exclusion categories and taking into account the interrelationships between keywords. Results - Exercise therapy is able to increase muscle mass and act as an alternative therapy in cases of metabolic disorders that cause muscle wasting. Exercise therapy that can be used to increase muscle mass is resistance training and controlled exercise programs. Conclusion - Exercise therapy is able to increase signaling activation of insulin growth factor (IGF1) which causes an increase in insulin sensitivity to improve the downregulation process of muscle wasting in patients with metabolic system disorders.